Improvement yield and nitrogen uptake of wheat through application of organic and inorganic fertilizers (Progressive Agriculture, 2016)
An experiment was conducted at the Soil Science Field Laboratory of Bangladesh Agricultural University, Mymensingh during winter (Rabi) season of 2013-14 to evaluate the effect of integrated use of organic and inorganic fertilizers on the growth, yield and nitrogen (N) uptake of wheat. There were six treatments such as T0 (control), T1 [STB-CF (HYG)], T2 [STB-CF (HYG) + CD (5 t/ha)], T3 [STB-CF (HYG) +PM (3 t/ha)], T4 [STB-CF (HYG) COM (5 t/ha)] and T5 [FP (Farmers practice)]. The experiment was laid out in a Randomized Complete Block Design with four replications. Soil test based nitrogen, phosphorus, potassium, sulphur, zinc and boron were used @ 100, 20, 60, 10, 3 and 2 kg ha-1, respectively. The integrated use of organic and inorganic fertilizers significantly increased the yield attributes as well as grain and straw yields of wheat. The treatment T3 [STB-CF (HYG) + PM (3 tha-1)] produced the highest grain yield of 3554 kg ha-1 (69.67% increase over control) and straw yield of 3635 kg ha-1 (62.83% increase over control). The lowest grain yield (2094 kg ha-1) and straw yield (2232 kg ha-1) were found in control treatment. The N content and uptake by wheat were also markedly influenced by combined use of organic and inorganic fertilizers and the treatment T3 demonstrated superior performance to other treatments. So, the applications of fertilizers in combination with poultry manure @ 3 t ha-1 can be used for the successful cultivation of wheat in Old Brahmaputra Floodplain soil. Progressive Agriculture 27 (2): 149-153, 2016